PESEM socio-business educational project a bet to train, captivate and educate the public of interest of the cooperative of the department of Cauca CODELCAUCA - Realpe-Leyton, Mireya; Barreda-Ramírez , Concepción (Universidad Francisco de Paula Santander, 2019)
The research carried out responds to the need to establish a proposal for a Social and Business Educational Project (PESEM) for the CODELCAUCA Cooperative, an entity in the solidarity sector that has offered its services 42 years ago and is the largest local Cooperative in the Department of Cauca, the research Its objective is to build a training proposal that fosters the culture of the solidarity economy and improves the member's sense of belonging, designing pertinent pedagogical strategies that promote their participation, proposing a series of training alternatives aimed at improving educational aspects. The methodology used is framed within a descriptive quantitative and qualitative approach, using research tools such as the interview, conversational interaction and the survey of 350 associates; The current situation of the organization was known and based on it, the PESEM was carried out for the entity, its development allowed identifying the training needs present among the members and other members of the Cooperative, as a result of the socio-economic changes that have been developed in recent years, likewise, the important role that information and communication technologies play in educational processes is evident today.